Conceptual changes in scientific argumentation through guided group settings - Lee, Ling Heng (2014)
The main goal of scientific argumentation is to foster students’ understanding of scientific concepts (von Aufschnaiters et al., 2008; Nussbaum, 2011; Sadler, 2004; Zohar and Nemet, 2002) and to eliminate alternative frameworks (Cross et al., 2008). The involvement of students in argumentative activities also enhances their scientific reasoning skills (Osborne et al., 2004). In order to induce conceptual changes through collaboration, instructional intervention are usually conducted following the socio-cognitive conflict design (Amigues, 1988). This design is based on the idea whereby the pairing of students with different initial conceptions will lead to their cognitive conflict. As a result, they will then seek for equilibrium to accommodate their naive concepts as scientific concepts. According to Kendeou and Broek (2007), when students’ existing concepts are activated and integrated with a scientific explanation, this will lead to an imbalance. The identification of this imbalance will trigger deeper information processing that causes conceptual changes. Mason (1996) stressed that conceptual change is likely to occur when students are asked to clarify, explain, and defend their own ideas.